2006
DOI: 10.1111/j.1467-842x.2006.tb00776.x
|View full text |Cite
|
Sign up to set email alerts
|

Occupational injuries by hour of day and day of week: a 20‐year study

Abstract: Most epidemiological studies are based on the classic triad of host, agent and environment. In injury epidemiology, a further parameter is available, that of time of occurrence. In an earlier study 1 based on data for Queensland for the three financial years 1969/70 to 1971/72, it was shown that: (a) there were more occupational injuries in the mornings of every weekday than in the afternoons; and (b) occupational injuries occurred most frequently on Mondays, with 23% of the weekly total. The corresponding fig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
18
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 9 publications
(6 reference statements)
6
18
0
Order By: Relevance
“…Similar findings concerning work-related injuries have been observed by Wigglesworth [2006] in a study of compensation claims in Australia. Similar findings concerning work-related injuries have been observed by Wigglesworth [2006] in a study of compensation claims in Australia.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar findings concerning work-related injuries have been observed by Wigglesworth [2006] in a study of compensation claims in Australia. Similar findings concerning work-related injuries have been observed by Wigglesworth [2006] in a study of compensation claims in Australia.…”
Section: Discussionsupporting
confidence: 87%
“…We found that the number of amputations decreased later in the week compared to early in the week. Similar findings concerning work-related injuries have been observed by Wigglesworth [2006] in a study of compensation claims in Australia. This temporal finding, although interesting, is difficult to interpret and its application to intervention efforts remain unclear.…”
Section: Discussionsupporting
confidence: 87%
“…This goes against many similar studies in forestry. For example, Lagerstrom et al (2017) [39], Laschi et al (2016) [8], Tsioras et al (2014) [15], and Wigglesworth (2006) [42] all state that accidents occur on Monday most frequently, reporting that more than one-fifth of all accidents occur on this day. The differences between accident frequency during particular workweek days proved to be insignificant in our case, as approximately one-fifth of all accidents occurred on Monday and Tuesday.…”
Section: Discussionmentioning
confidence: 99%
“…Population-based surveys, such as those initiated by the Bureau of Labor Statistics, emergency department surveillance systems, and state worker compensation claims are frequently the main sources of information for nonfatal occupational injury research [Layne and Pollack, 2004;Friedman and Forst, 2007;McCall and Horwitz, 2006;Mujuru et al, 2006;Wigglesworth, 2006]. While these databases are valuable sources of data, many of them lack information on key potential confounders.…”
Section: Introductionmentioning
confidence: 98%